X-Git-Url: http://lambda.jimpryor.net/git/gitweb.cgi?p=lambda.git;a=blobdiff_plain;f=cps.mdwn;h=6668b48ce1bcde7c63aed5a13b113c376e4bc884;hp=f869b7956f4f86e6a95309301c07d3fff8207075;hb=339a5442b568742f36ddab4a44f77cfb26b609a2;hpb=54360af5dafc49cca9e484ecdc74c26c4adfb65c;ds=sidebyside diff --git a/cps.mdwn b/cps.mdwn index f869b795..6668b48c 100644 --- a/cps.mdwn +++ b/cps.mdwn @@ -69,16 +69,16 @@ what the CPS is doing, and how. In order for the CPS to work, we have to adopt a new restriction on beta reduction: beta reduction does not occur underneath a lambda. That is, `(\x.y)z` reduces to `z`, but `\u.(\x.y)z` does not reduce to -`\w.z`, because the `\w` protects the redex in the body from -reduction. (In this context, a redex is a part of a term that matches +`\u.z`, because the `\u` protects the redex in the body from +reduction. (In this context, a "redex" is a part of a term that matches the pattern `...((\xM)N)...`, i.e., something that can potentially be the target of beta reduction.) Start with a simple form that has two different reduction paths: -reducing the leftmost lambda first: `(\x.y)((\x.z)w) ~~> y` +reducing the leftmost lambda first: `(\x.y)((\x.z)u) ~~> y` -reducing the rightmost lambda first: `(\x.y)((\x.z)w) ~~> (\x.y)z ~~> y` +reducing the rightmost lambda first: `(\x.y)((\x.z)u) ~~> (\x.y)z ~~> y` After using the following call-by-name CPS transform---and assuming that we never evaluate redexes protected by a lambda---only the first @@ -91,7 +91,7 @@ Here's the CPS transform defined: [\xM] = \k.k(\x[M]) [MN] = \k.[M](\m.m[N]k) -Here's the result of applying the transform to our problem term: +Here's the result of applying the transform to our simple example: [(\x.y)((\x.z)u)] = \k.[\x.y](\m.m[(\x.z)u]k) = @@ -109,13 +109,15 @@ trivial continuation, usually the identity function `I = \x.x`. [\x.y](\m.m[(\x.z)u] I) = (\k.k(\x.y))(\m.m[(\x.z)u] I) * * - (\x.y)[(\x.z)u] I + (\x.y)[(\x.z)u] I --A-- * y I The application to `I` unlocks the leftmost functor. Because that -functor (`\x.y`) throws away its argument, we never need to expand the -CPS transform of the argument. +functor (`\x.y`) throws away its argument (consider the reduction in the +line marked (A)), we never need to expand the +CPS transform of the argument. This means that we never bother to +reduce redexes inside the argument. Compare with a call-by-value xform: @@ -125,7 +127,7 @@ Compare with a call-by-value xform: This time the reduction unfolds in a different manner: - {(\x.y)((\x.z)w)} I = + {(\x.y)((\x.z)u)} I = (\k.{\x.y}(\m.{(\x.z)u}(\n.mnk))) I * {\x.y}(\m.{(\x.z)u}(\n.mnI)) = @@ -140,7 +142,7 @@ This time the reduction unfolds in a different manner: {u}(\n.(\x.{z})n(\n.(\x.{y})nI)) = (\k.ku)(\n.(\x.{z})n(\n.(\x.{y})nI)) * * - (\x.{z})u(\n.(\x.{y})nI) + (\x.{z})u(\n.(\x.{y})nI) --A-- * {z}(\n.(\x.{y})nI) = (\k.kz)(\n.(\x.{y})nI) @@ -152,6 +154,9 @@ This time the reduction unfolds in a different manner: * I y +In this case, the argument does get evaluated: consider the reduction +in the line marked (A). + Both xforms make the following guarantee: as long as redexes underneath a lambda are never evaluated, there will be at most one reduction available at any step in the evaluation. @@ -216,9 +221,9 @@ for functional types a->b, (a->b)' = ((a' -> σ) -> σ) -> (b' -> &sig Terms Types - [x] = \k.xk [a] = (a'->σ)->σ - [\xM] = \k.k(\x[M]) [a->b] = ((a->b)'->σ)->σ - [MN] = \k.[M](\m.m[N]k) [b] = (b'->σ)->σ + [x] = \k.xk [a] = (a'->o)->o + [\xM] = \k.k(\x[M]) [a->b] = ((a->b)'->o)->o + [MN] = \k.[M](\m.m[N]k) [b] = (b'->o)->o Remember that types associate to the right. Let's work through the application xform and make sure the types are consistent. We'll have @@ -227,14 +232,14 @@ the following types: M:a->b N:a MN:b - k:b'->σ - [N]:(a'->σ)->σ - m:((a'->σ)->σ)->(b'->σ)->σ - m[N]:(b'->σ)->σ - m[N]k:σ - [M]:((a->b)'->σ)->σ = ((((a'->σ)->σ)->(b'->σ)->σ)->σ)->σ - [M](\m.m[N]k):σ - [MN]:(b'->σ)->σ + k:b'->o + [N]:(a'->o)->o + m:((a'->o)->o)->(b'->o)->o + m[N]:(b'->o)->o + m[N]k:o + [M]:((a->b)'->o)->o = ((((a'->o)->o)->(b'->o)->o)->o)->o + [M](\m.m[N]k):o + [MN]:(b'->o)->o Be aware that even though the transform uses the same symbol for the translation of a variable (i.e., `[x] = x`), in general the variable